Formation process of holey graphene and its assembled binder-free film electrode with high volumetric capacitance. (1st January 2016) - Bai, Yonglong; Yang, Xiaofan; He, Yibo; Zhang, Jinyang; Kang, Liping; Xu, Hua; Shi, Feng; Lei, Zhibin; Liu, Zong-Huai
Graphical abstract: Holey graphene has been prepared through a relatively low temperature hydrothermal reaction between GO and H2 O2 without sacrificing its dispersity. In virtue of the superior dispersity and processability of the resultant material, the binder-free film electrodes with high packing density can be directly assembled by simple vacuum filtration. The optimum holey graphene film electrode exhibits high volumetric capacitance of 216 F cm −3 at a current density of 1 A g −1 while retaining an enhanced rate capability in 6 M KOH electrolyte. Highlights: Holey graphene has been prepared through a mild and eco-friendly route. The resultant holey graphene exhibits superior dispersity. The binder free film electrode can be directly assembled by vacuum filtration. The film electrode delivers high volumetric capacitance and rate capability. Abstract: Holey graphene with abundant in-plane nanopores is achieved through a mild defect-etching reaction between graphene oxide (GO) and hydrogen peroxide (H2 O2 ) then followed by a reduction process in hydrazine solution. The porosity of the obtained holey graphene is systematically investigated by optimizing the reaction conditions between GO and H2 O2 . The optimum reaction conditions are that GO is hydrothermally treated in 0.4 mL H2 O2 at 100 °C for 10 h and the as-prepared holey graphene oxide (HGO) is refluxed in hydrazine solution at 100 °C for 1 h, by which holey reduced graphene oxide (HRGO) suspension with good dispersity is obtained. By vacuum filtration of the HRGO suspension, the binder-free porous graphene film electrodes are successfully assembled. The obtained film electrodes exhibit high specific capacitance (251 F g −1 at a current density of 1 A g −1 ), high volumetric capacitance (up to 216 F cm −3 ), and enhanced rate capability (73% capacitance retention from 1–60 A g −1 ) due to their high packing density (0.86 g cm −3 ). The suitable porosity of the assembled porous graphene film keeps a balance between electrolyte ion diffusion rate and conductivity, which can bridge the gap between gravimetric capacitance and volumetric capacitance for the obtained electrode material.